Adherence to 24-h movement guidelines in Spanish schoolchildren and its association with insulin resistance: a cross-sectional study - Salas-González, María Dolores; Bermejo, Laura M.; González-Rodríguez, Liliana G.; Lozano-Estevan, María Del Carmen; Ortega, Rosa M.; López-Sobaler, Ana M. (Frontiers in Public Health, 2023)
Introduction: Being more active, being less sedentary, and sleeping enough are associated with adequate body weight and adiposity in children. However, few researchers have analysed these different lifestyle behaviours and the adherence to 24 h movement guidelines with respect to insulin resistance (IR) at school age. Therefore, we aimed to analyse the association between the adherence to 24 h movement guidelines (physical activity, sedentary time, sleep) and insulin resistance (IR) in Spanish schoolchildren. Methods: A cross-sectional study of 839 children (8-13 years, 51.1% girls) were studied. Anthropometric, biochemical, and lifestyle behavioural data were collected. IR was defined as HOMA-IR>3.16. Compliance with the 24 h movement guidelines were defined as ≥60 min/day of moderate and/or vigorous physical activity, ≤120 min/day of screen time, and 9-11 h/day of sleep time. Associations between adherence to the 24 h movement guidelines and IR were performed by multivariate logistic regression analyses. Results: The IR in our sample was 5.0%, being higher in girls. Compliance with physical activity or screen time, but not with sleep recommendations, was associated with lower fasting glucose, fasting insulin, and HOMA-IR values. A low adherence to 24 h movement guidelines was associated with a higher risk of IR (odds ratio (95% CI): 2.150 [1.089-4.247]), especially in girls (odds ratio (95% CI): 2.800 [1.180-6.645]). Conclusions: Higher physical activity levels and lower screen times were associated with a lower risk of IR in schoolchildren, underlining the importance of adhering to as many healthy lifestyle recommendations as possible.